2010
DOI: 10.1021/jo9025429
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of a Hypervalent Iodine Trifluoromethylating Reagent toward THF: Ring Opening and Formation of Trifluoromethyl Ethers

Abstract: 1-Trifluoromethyl-1,2-benziodoxol-3-(1H)-one (1) is able to transfer the electrophilic CF(3) group to the oxygen atom of THF in the presence of a Lewis or Bronsted acid. This results in a new ring-opening reaction of THF yielding trifluoromethyl ethers. Details of this reaction and the insight gained into the mechanism of action of reagent 1 are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 42 publications
3
36
0
2
Order By: Relevance
“…Therefore, it is reasonable to assume that the ratedetermining step of the reaction involves the protonated form of reagent 1 and CD 3 CN. This is in line with our previous observations concerning the trifluoromethylation of THF [15] and toluenesulfonic acid. [11] On the basis of these rate studies and our previous experience with these systems, we propose the mechanism shown in Scheme 3.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is reasonable to assume that the ratedetermining step of the reaction involves the protonated form of reagent 1 and CD 3 CN. This is in line with our previous observations concerning the trifluoromethylation of THF [15] and toluenesulfonic acid. [11] On the basis of these rate studies and our previous experience with these systems, we propose the mechanism shown in Scheme 3.…”
supporting
confidence: 93%
“…Thus, as an example, the structure of compound 4 in solution was determined by multinuclear NMR methods. Figure 2 shows sections of the corresponding 19 F, 15 The structure of the two constitutional isomers 8 and 9 were determined in solution by analogous NMR methods and confirmed by X-ray analysis. Corresponding ORTEP representations and selected geometrical parameters are shown in Figure 3.…”
mentioning
confidence: 89%
“…In contrast, phenols experiment trifluoromethylation predominantly at the aromatic positions [82]. The latter trifluoromethylation reagent also promoted ringopening of tetrahydrofuran to form oligomeric trifluoromethyl ethers [83].…”
Section: Trifluoromethylation Of Sp 3 Nitrogen Oxygen and Sulfurmentioning
confidence: 99%
“…[22] The trifluoromethylation of other hydroxylated compounds were also investigated. [22] The trifluoromethylation of other hydroxylated compounds were also investigated.…”
Section: Electrophilic Trifluoromethylation Of Alcohols or Hydroxylatmentioning
confidence: 99%